Early intervention in viper bites: a potential strategy to mitigate acute kidney injury and its long-term consequences - Mushtaq, Rabeea; Ramlah Naz; Mehreen Fatima (Journal of the Pakistan Medical Association, 2024)
Dear Editor, By this letter we intend to highlight the close association between snake bites and acute kidney injury, as the causative snakes are common natives of Tropical regions and a common cause of death because of being poorly managed. Snake bites are a significant cause of acute kidney injury in tropical regions, particularly in Eastern Pakistan, where Russell’s viper, a common cause, is prevalent. The farmlands of Sindh and Balochistan are predisposed to snake bites due to their favorable weather and vast fields. A 2020 study found 454 snakebite cases in Southern Sindh, with 6 deaths. The most common mechanisms are venom-mediated consumption coagulopathy (VMCC) and endothelial damage, leading to systemic bleeding diathesis and decreased perfusion of end organs. Long-term effects of snake bites include worsening renal conditions and progression towards end-stage renal disease. Eastern Pakistan commonly harbors Russell’s viper- a frequent cause of snakebite-associated mortality, which belongs to the Viperidae family and is famously known to produce vasculotoxic venom. (1) The farmlands of Sindh and Balochistan are predisposed to snake bites as the weather of these regions and the vast fields allow the vipers to flourish and thrive well. A study conducted in 2020, representing the population of Southern Sindh, demonstrated a total of 454 cases of snakebite in a span of 1 year, out of which 6 victims died. (2) Since the prevalence of vipers is common in the district of Sindh, the deaths could be attributable to the hemorrhagic manifestations of vipers’ bites. The most significant mechanisms underlying viper bite presentations are venom-mediated consumption coagulopathy (VMCC) and endothelial damage resulting in systemic bleeding diathesis, which together contribute to decreased perfusion of end organs like the heart, kidneys, brain, or gastrointestinal system. (3) VMCC is a major contributor to acute kidney injury (AKI), a common outcome of vasculotoxic snake bites, along with enzymatic dissolution of the glomerular basement membrane (BM) by the venom metalloproteinases. (4) The hemorrhagic deterioration of the vessels leads to ischemic nephropathy, and the impaired BM allows proteinuria, hemoglobinuria, and increased creatinine, often predisposing the victim to timely dialysis. A study concluded that individuals with co-morbidities are more susceptible to developing long-term effects of snake bites like worsening renal conditions such as new-onset hypertension, dialysis dependence, and end-stage renal disease. (5) —Continue